Penggunaan Aturan Ular Tangga dalam Musik Aleatorik Berbasis Serialisme Integral - Yayi Wira Pamungkas (Journal of Music Science, Technology, and Industry, 2020)
Purpose: The author does an experiment by using the rules of snake and ladder to find out and understand how the concept of uncertainty can work in serialism-based aleatoric music: by testing it using the most stringent serialism system, namely the system of integral serialism. Research methods: The process of creating the composition of this artistic research work has five stages, namely the exploration stage, the concept preparation stage, the concept analysis stage, the macro structure preparation stage, and the concept application stage. Results and discussion: The concept of snake and ladder can optimize the concept of uncertainty in serialism-based aleatoric music. The integral serialism system dominates the formation of melody and harmony, while the concept of snake and ladder that is aleatoris is used as phrase control. Implication: There are two phenomena that stimulate the creation of the idea of creation of this artistic research work, namely the problem of stiffness and weak characteristics of the concept of uncertainty in serialism-based aleatoric music.